On lower bounds for Poisson approximation to 2-runs statistic - Petrauskienė, Jūratė; Čekanavičius, Vydas (Lietuvos matematikos rinkinys, 2010)
Two-runs statistic is approximated by various compound Poisson distributions and second order asymptotic expansions. Estimates of lower bounds are obtained for the uniform Kolmogorov and local metrics.
Keywords: 2-runs; compound Poisson distribution; m-dependent variables; uniform Kolmogorov norm; local norm